GAMBARAN KEMAMPUAN KERJA PETUGAS TERHADAP PENGELOLAAN REKAM MEDIS RSKD IBU DAN ANAK PERTIWI MAKASSAR TAHUN 2022 - Irna Irna; Dian Ekawaty; Mohammad Ardani Samad; Nurmulia Wunaini Ngkolu (Institut Kesehatan Pelamonia, 2024)
Workability is how he is able to do his job by taking into account the demands of the job, health and mental resources. A person's ability will be determined by the level of education, training and experience because of these three elements, knowledge and skills can be obtained. The purpose of this research is to describe the work ability of officers in managing medical records at the Mother and Child Hospital in Makassar in 2022. This study uses descriptive qualitative methods. The informants in this study amounted to 6 respondents consisting of the hospital director, the head of the medical record installation and 4 medical record officers. The data in this study were taken through interviews and direct observation. Based on the results of the research, work ability is still not maximized because educational qualifications do not match the specified so that it can result in incorrect file insertions and medical record management training programs for officers do not run so that officers also lack knowledge and data information updates which can result in delays in completing reports, but there are still informants who provide information that there is no incoming training application letter, and different information is given to key informants that the medical record unit has never submitted a training application letter to us.